INTRODUCTION TO VOLUME 7 : 2009 - Hashim, Norliza (PLANNING MALAYSIA, 2016)
Planning Malaysia has achieved another major milestone for the Malaysian Institute of Planners. It reaches out today beyond the circulation of MIP Members and beyond the boundaries of our country. It is now circulated to various libraries, planning and related professions organisations, planning schools and universities all across the globe. Every article in this journal is refereed by distinguished panel of local and international professionals related to the planning profession. This adds credibility to the journal and ensures that every article published achieves the desired level of quality as well as meets the international standards of publication. Planning Malaysia has come a long way from its first inaugural publication. Much credit must be given to the effort and continuous passion of the Chief Editor - Professor Dr Alias Abdullah and his dedicated editorial team. They have continued to enhance the quality of the journal as well as increase its level of circulation. This is part of MIP’s mission for continuous effort in knowledge sharing and promotion of town planning and its professionals. It is my deepest aspiration that Planning Malaysia becomes a household name to the planning community. Thus it is hoped that all members take this opportunity to contribute articles to the journal as its widespread circulation will enable members to disseminate ideas, share new findings or planning theories or share experiential planning to the industry at large. Thank you to all writers, editorial board as well as the referees of the articles. I pray that the contribution that you all have made to the journal will shower all with greater wealth of knowledge and contentment. Thank you.